Maridjan Menang Taruhan (Analisis Antropologis terhadap Pertarungan Agama-Budaya Maridjan pada 2006) - A Zaenurrosyid (Balai Penelitian dan Pengembangan Agama Semarang, 2013)
This research was generally based on an interesting phenomenon in 2006, when Merapi erupted. There was Maridjan’s rebellion as a royal servant to climb down from Merapi when Hamengkubuwono X as the king commanded him. The main questions were what were the factors of Maridjan’s resistances?; what were the forms of Maridjan capitals in this fighting?; and what did Maridjan get from the bet as the winner? The approach of this research was anthropological perspective using participatory observation and analyzed by qualitative method. To get data, researcher lived in Maridjan’s house for several months in Merapi. The findings of the study were there was Maridjan’s resistance which was interpreted as a fighting created by media. The second was Maridjan’s resistance supported by two capital powers; the cultural power as the Merapi’s caretaker and the discourse capital supported by the media. The third was Maridjan won the bet by getting the prestige in his social status either popularities or wealth.